2001
DOI: 10.1002/path.976
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow contributes to renal parenchymal turnover and regeneration

Abstract: In order to establish whether extra-renal cells contribute to the turnover and repair of renal tissues, this study examined kidneys of female mice that had received a male bone marrow transplant and kidney biopsies from male patients who had received kidney transplants from female donors. By using in situ hybridization to detect Y-chromosomes it could be demonstrated that circulating stem cells frequently engraft into the kidney and differentiate into renal parenchymal cells. In the human renal grafts it was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
449
1
8

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(479 citation statements)
references
References 21 publications
(33 reference statements)
19
449
1
8
Order By: Relevance
“…It has long been proposed that bone marrow, a known source of stem cells, might be able to contribute to the repair of other organs [17]. Early reports noted the presence of bone marrow-derived cells in the kidney, using sex-mismatching of bone marrow donor and recipient [18]. Additionally, it was noted by Imasawa et al [19] that mice with a spontaneous presentation of IgA nephropathy showed disease amelioration after bone marrow transplantation from an unaffected donor.…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…It has long been proposed that bone marrow, a known source of stem cells, might be able to contribute to the repair of other organs [17]. Early reports noted the presence of bone marrow-derived cells in the kidney, using sex-mismatching of bone marrow donor and recipient [18]. Additionally, it was noted by Imasawa et al [19] that mice with a spontaneous presentation of IgA nephropathy showed disease amelioration after bone marrow transplantation from an unaffected donor.…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…23 We have also found occasional male endothelial cells in female kidneys grafted into male recipients, 16 however other groups have reported no evidence of revascularization by the recipient, even in cases where the transplant failed. 24 …”
Section: Kidney Endotheliummentioning
confidence: 57%
“…We have used in situ hybridization for the Y chromosome in female mice that have received male whole bone marrow transplants to demonstrate the bone marrow origin of a wide range of kidney cell types, including tubular epithelial cells (Figure 1e), interstitial cells and podocytes. 16 Other groups have found evidence for the mesangial cell differentiation of BMSCs. 17 In our studies, up to 8% of the renal tubular epithelium was found to be of bone marrow origin.…”
Section: Renal Differentiation From Blood-borne Stem Cellsmentioning
confidence: 99%
“…One recent study showed that highly purified hematopoietic stem cells even have the potential to differentiate into muscle [19] . Moreover, Poulsom et al [24] found that bone marrow cells could differentiate into both epithelial cells of the renal tubule and podocytes of glomerulus in the adult mouse kidney. Taken together, the pluripotency has been confirmed in most stem cells types.…”
Section: Discussionmentioning
confidence: 99%